If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(c + -8) = 8 Reorder the terms: -1(-8 + c) = 8 (-8 * -1 + c * -1) = 8 (8 + -1c) = 8 Add '-8' to each side of the equation. 8 + -8 + -1c = 8 + -8 Combine like terms: 8 + -8 = 0 0 + -1c = 8 + -8 -1c = 8 + -8 Combine like terms: 8 + -8 = 0 -1c = 0 Solving -1c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-1'. c = 0 Simplifying c = 0
| X^2+2=x+28 | | 6x+5=17+2 | | 9-3(4-11x)=(5x+2)*6-12 | | Y*Y+10y-39=0 | | 904/100 | | 4(a-6)=52 | | (3x+1)+(5x+3)= | | (5x+2)*6=24 | | 0.2=4/(5x-15) | | (8x-7)(3x+10)= | | -x^2+21x+24=0 | | 2x+2x=-56 | | 3x+x+x-10=180 | | Log9x=-3/2 | | 21/12/4 | | a^2-24a+96=0 | | 4+5(p-1)=34+2 | | 4+5(p+1)=34+2 | | 3(5x-4)=28 | | sqrt(x^2+9)-sqrt(x^2-7)=2 | | ln^2x=t | | 22=(y+5)(3y-2) | | 25*1.16=29 | | a^2/2a | | 26x^2-260x+546=0 | | a^2b/2a | | 5(4x-2)=2(8x+1) | | 9x^2+6kx+4k=0 | | 8x-4=4x+9 | | 2a-4b+2=2 | | 0.47=X/1000 | | 5x+13=-47-4x |